Pembrolizumab Plus Chemotherapy for Chinese Patients With Metastatic Squamous NSCLC in KEYNOTE-407 - Ying Cheng, MD (JTO Clinical and Research Reports, 2021)
Introduction: Pembrolizumab plus chemotherapy significantly improved survival outcomes versus placebo plus chemotherapy in patients with previously untreated metastatic squamous NSCLC in the randomized, double-blind, phase 3 KEYNOTE-407 study. We present the results of Chinese patients enrolled in the KEYNOTE-407 global and China extension studies. Methods: Patients enrolled from mainland China in the KEYNOTE-407 global (NCT02775435) and China extension studies (NCT03875092) were randomized 1:1 to 35 cycles of pembrolizumab or placebo plus four cycles of carboplatin and paclitaxel or nab-paclitaxel. Dual primary end points were overall survival (OS) and progression-free survival (PFS) (based on the Response Evaluation Criteria in Solid Tumors version 1.1 by blinded independent central review). Results: A total of 125 patients were randomized (pembrolizumab–chemotherapy, n = 65; placebo–chemotherapy, n = 60). As of September 30, 2020, median (range) study follow-up was 28.1 (25.1‒40.9) months. Pembrolizumab–chemotherapy improved OS (hazard ratio [HR] = 0.44, 95% confidence interval [CI]: 0.28–0.70) and PFS (HR = 0.35, 95% CI: 0.24–0.52) versus placebo–chemotherapy. Two-year OS and PFS rates for pembrolizumab–chemotherapy versus placebo–chemotherapy were 56.9% versus 31.7% and 24.2% versus 3.3%, respectively. Treatment-related grade 3 to 5 adverse events occurred in 81.5% and 81.7%, respectively. Relative to baseline, pembrolizumab–chemotherapy improved global health status/quality of life scores at week 18 versus placebo–chemotherapy (difference in least squares means = 7.6, 95% CI: 1.5–13.7) and prolonged time to deterioration in cough, chest pain, or dyspnea (HR = 0.50, 95% CI: 0.28–0.89). Conclusions: Pembrolizumab–chemotherapy prolonged survival versus placebo–chemotherapy with manageable toxicity and preserved or improved health-related quality of life in Chinese patients with metastatic squamous NSCLC. These findings support pembrolizumab–chemotherapy as first-line therapy in this population.